Africana critical theory : reconstructing the black radical tradition, from W.E.B. Du Bois and C.L.R. James to Frantz Fanon and Amilcar Cabral - Rabaka, Reiland, 1972- (Lexington Books, 2009)
Africana Critical Theory innovatively identifies and analyzes continental and diasporan African contributions to classical and contemporary critical theory through the works of W.E.B. Du Bois, C.L.R. James, Aime Cesaire, Leopold Senghor, Frantz Fanon, and Amilcar Cabral.